PENGARUH PIJAT TANGAN DAN AROMATERAPI LAVENDER TERHADAP TINGKAT KECEMASAN MAHASISWA SEBELUM UJIAN LAB KLINIK KEPERAWATAN - Rawiti NMR (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2014)
Nursing skill lab is media practice to show hospital image for nursing students. Because of that, anxiety in nursing students can occur before facing nursing skill lab tests. The hands massage and lavender aromatherapy can provides relaxation and minimizes sympathetic nervous activity in the autonomic nervous system. Adrenaline and cortisol will decrease stress of students. This study aimed to determine the effect of hands massage and lavender aromateraphy for anxiety level on nursing students in Nursing Department, Medical Faculty of Udayana University Class of 2013 before facing nursing skill lab tests. This is Quasy-experimental design with pre-test and post-test with control group design. Sample consist of 30 nursing students were selected with simple random sampling technique, divided become two groups, which are the control group and the treatment group. The treatment group was given the hands massage and lavender aromatherapy for 20 minutes. Both of groups was measured by using a questioners of anxiety level, this instrument is Taylor Manifest Anxiety Scale (TMAS) (0-40) for examine pre-test and post-test anxiety level. Research results based on analysis by the Man Whitney U Test, this difference is statistically significant, with p-value=0,031, which means that there is effects of hands massage and lavender aromatherapy for anxiety level on nursing students on Nursing Department, Medical Faculty of Udayana University Class of 2013.